Early keratinocyte differentiation on micropillar interfaces - Steinberg, Thorsten; Schulz, Simon; Spatz, Joachim P.; Grabe, Niels; Wörtche, Eva; Kohl, Annette; Komposch, Gerda; Tomakidi, Pascal (Nano letters, 2007)
We employed topographical patterning to analyze early keratinocyte differentiation on top of microfabricated pillar arrays. Fibronectin immobilized on pillar “heads” yielded a nucleus-associated granular keratin 1 (K1) pattern in immortalized human gingival keratinocytes (IHGK) at pillar interspaces of 14 μm. Decreasing distances of 11and 8 μm revealed cytoplasmic extension of the early differentiation marker K1 on poly(dimethylsiloxane) (PDMS) pillars. The most extensive cytoplasmic K1 protein distribution noted at the smallest pillar scale coincided with higher ratios of K1 mRNA gene transcription. These experiments suggest that early keratinocyte differentiation was governed by the topographical characteristics of the pillar pattern. Moreover, they form the basis to study cell functions such as differentiation in a defined topologically structured environment.
Published on Web 12/22/2006
Gesehen am 17.03.2021